Integration of non-energy among the end-use demands of bottom-up whole-energy system models - Rixhon, Xavier; Tonelli, Davide; Colla, Martin; Verleysen, Kevin; Limpens, Gauthier; Jeanmart, Hervé; Contino, Francesco (Frontiers in Energy Research, 2022)
The complexity of bottom-up energy system models has progressively grown to enhance the representativeness of the system under analysis. Among them, whole-energy system models aim at representing the energy resources, conversion technologies, and energy demands of regions (i.e., a country) in its entirety. Despite this effort leading to an increased number of conversion processes modeled, the typologies of the end-use demand have remained limited to three categories: electricity, heat, and transportation. A fourth category, herein addressed as the non-energy demand, has widely been neglected. Being associated with the production of chemicals (i.e., plastics and fertilizers), the non-energy demand represents 10% of the world’s total end-use demand. Its relevance becomes fundamental in analyses that define the optimal defossilization pathways of energy systems with high dependence on fossil resources. This contribution introduces a schematic representation of the conversion processes involved in the satisfaction of the non-energy demand. Through its implementation in a bottom-up whole-energy system model, it evaluates the impact of this additional end-use in the configuration of the optimal energy system. In this study, the Belgian energy system, characterized by a penetration of the chemical and the petrochemical industries up to 20% of its total end-use demand, is taken as a reference case. The transition to a defossilized energy system is enforced through a snapshot analysis with a progressively more restrictive emissions cap. The results emphasize the role of renewable carriers (i.e., methanol and ammonia) in the defossilization of the energy system, otherwise hindered when the non-energy demand is neglected. The 100% import of these carriers at the lowest emissions cap highlights the potential dependence of the country under analysis, with limited availability of renewable resources, from countries exporting renewable methanol and ammonia.